(untitled) (Research, Society and Development, 2022)
In Indonesia, thesis is a scientific paper written by prospective undergraduates as a requirement to obtain a bachelor’s degree in an undergraduate study program which of course in the process often experiences anxiety which will affect the performance of students on campus, especially students of the Faculty of Medicine. This study aims to determine the level of anxiety in the implementation of student essay at the Faculty of Medicine, Udayana University. This research is a descriptive research with survey method. The number of samples is 170 respondents and sampling method using random sampling technique. The results of the study showed the prevalence of anxiety levels in students of the Faculty of Medicine, Udayana University class 2017 in the mild category as many as 135 people (79.4%), the moderate category as many as 31 people (18.2%) and the high category as many as 4 people (2.4%). For each study program, the level of anxiety experienced is relatively the same, the highest category in the mild category, then followed by the moderate category and the last with the smallest number, namely the high category.